Heavy Metals Contamination and the Evolution of Environmental Policy: A Comprehensive Bibliometric Reviews - Nofriandi, Alwi; Frinaldi, Aldri; Lanin, Dasman; Rembrandt, Rembrandt; Yulkifli, Yulkifli; Dewata, Indang; Siregar, Dewi Rahmadani; Insani, Munadia; Sati’at, Nur Anisa; Febrina, Suci (Science and Environmental Journal for Postgraduate, 2024)
This study investigates the relationship between heavy metal pollution and environmental policy through a bibliometric analysis of research published between 2009 and 2023. Heavy metal contamination, involving toxic elements such as lead, cadmium, and mercury, poses significant risks to human health and ecosystems, particularly in areas of intensive industrial activity. The study aims to assess research trends, policy advancements, and collaborative networks to identify gaps and propose future directions. Data were extracted from Scopus, employing keywords like “heavy metals” and “environmental policy”. Biblioshiny software facilitated analyses of publication trends, geographic distribution, co-authorship networks, and citation impact. The findings reveal a marked increase in research output from 2015, driven by international policy initiatives like the Minamata Convention. China leads in publication volume, reflecting its industrial challenges, while other nations like India and Brazil emphasize collaborative efforts. Keyword analyses highlight themes such as health risks, pollution monitoring, and policy evaluation. The study underscores the critical role of global cooperation in addressing pollution through innovative technologies and effective policies.Future research should explore the impact of climate change on heavy metal mobility, long-term health effects, and the integration of AI and IoT in environmental monitoring. These steps are vital for advancing sustainable solutions to mitigate heavy metal pollution.